Effectiveness of Training Psychological Resilience on Aggression and Happiness among Students - Bahman Akbari (Journal of Holistic Nursing and Midwifery)
Introduction: Today, psychological methods are being applied more often to reduce adverse effects of social life and to enhance positive and satisfying effects of communal life.One of these methods is psychological resilience training.